Minimally invasive endoscopic foraminal decompression for adult degenerative scoliosis: clinical case study and literature review - Shamil Kh. Gizatullin; Sergey A. Bitner; Alexander S. Khristosturov; Ivan V. Volkov; Viacheslav Yu. Kurnosenko; Ilya P. Dubinin (Хирургия позвоночника, 2019)
Objective. To demonstrate opportunities of minimally invasive surgery in the treatment of deformities in patients with degenerative disease of the spine. Material and Methods. The clinical case of a 53-year-old female patient with adult degenerative scoliosis accompanied by foraminal stenosis and foraminal disc herniation at the L4–L5 level on the left with L5 root compression was considered. The clinical picture of the disease was carefully analyzed for compliance with the criteria for possibility of minimally invasive intervention as opposed to reconstructive surgery using instrumentation. The nature of the pain syndrome and its intensity according to VAS were determined, preoperative CT and MRI studies were carried out, and functional radiographs to detect signs of instability and the whole spine radiographs to calculate sagittal and coronal balance parameters were taken. A retrospective dynamic assessment of radiological data throughout the disease course was carried out to determine the dynamics of the deformity development. Postoperative follow-up was performed during 6 months. Pain syndrome was assessed according to VAS, and quality of life – according to Oswestry questionnaire. Postoperative CT and MRI studies were performed, and spinal radiographs were taken to calculate sagittal and coronal balance parameters. PubMed data and a number of meta-analyzes were considered to substantiate the choice of treatment. Results. Six months after surgery, the patient does not complain, is physically active, fully resumed work. She has not pain syndrome (VAS score 0), the Oswestry index is 8 points, neurological and static-dynamic statuses are without negative dynamics. The parameters of coronal and sagittal balance are stable. Conclusion. Endoscopic foraminal decompression may be the method of choice in the treatment of patients with adult degenerative scoliosis with a dominant clinical picture of monoradicular syndrome and compensated sagittal balance.